2021
DOI: 10.1177/03091333211057194
|View full text |Cite
|
Sign up to set email alerts
|

Coastal erosion in sandy beaches along a tectonically active coast: The Chile study case

Abstract: Coastal erosion in 45 sandy beaches covering nearly 2000 km along the tectonically active Chilean coast is assessed during the last four decades. The historical analysis is based on the assessment of decadal changes of the shoreline position extracted from topographic surveys, aerial photographs, satellite images and survey maps using the DSAS software. Results show that 80% of the sites presented erosion rates (>−0.2 m/y), 7% beaches accreted (>0.2 m/y) while 13% remained stable. Eroded beaches include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 87 publications
0
29
0
Order By: Relevance
“…Duan et al [89], on the coasts of China, clustered their coastal erosion and sedimentation results into rocky, beachy, muddy, and anthropic coasts. Martinez et al [90] carried out multi-temporal analyses for different beaches in Chile; their results are attributed to processes derived from local regional conditions, such as the different effects of seismic tectonics, e.g., tsunamis, the up-lift, and subsidence. Godwyn-Paulson et al [91] analyzed the effects on the coastline produced by the sea swell event, where new local conditions, such as geomorphology and bathymetry, are the predominant factors in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al [89], on the coasts of China, clustered their coastal erosion and sedimentation results into rocky, beachy, muddy, and anthropic coasts. Martinez et al [90] carried out multi-temporal analyses for different beaches in Chile; their results are attributed to processes derived from local regional conditions, such as the different effects of seismic tectonics, e.g., tsunamis, the up-lift, and subsidence. Godwyn-Paulson et al [91] analyzed the effects on the coastline produced by the sea swell event, where new local conditions, such as geomorphology and bathymetry, are the predominant factors in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Th were affected by two large earthquakes and their coseismic effects 6.9 (M which caused significant changes in the seafloor that could partially explai in the coastline and its dynamics. These changes, coseismic uplift/subside from post-tsunami studies, and source inversions, are detailed for these ear their effects on the coastal areas of Navidad and Pichilemu [71][72][73][74], wh changes can be highly variable in space and determined by changes in th addition, coseismic subsidence in combination with sea level rise en erosion, and coastal subsidence can induce accretion [75].…”
Section: Urban Areasmentioning
confidence: 99%
“…These changes, coseismic uplift/subsidence obtained from post-tsunami studies, and source inversions, are detailed for these earthquakes and their effects on the coastal areas of Navidad and Pichilemu [71][72][73][74], where coseismic changes can be highly variable in space and determined by changes in the coastline. In addition, coseismic subsidence in combination with sea level rise enhances beach erosion, and coastal subsidence can induce accretion [75].…”
Section: Urban Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid coastal changes after coseismic subsidence were observed after the 2010 Chile (Martínez et al, 2015(Martínez et al, , 2021, 2011 Tohoku (e.g., Tappin et al, 2012) and 2004 Sumatra-Andaman (e.g., Choowong et al, 2009;Liew et al, 2010;Monecke et al, 2015Monecke et al, , 2017 great earthquakes. These studies showed that, after coseismic subsidence, the shoreline typically receded by tens to hundreds of metres.…”
mentioning
confidence: 99%